Dynamic Adsorption And Regeneration Studies Of Acid Yellow 17 Using Modified Activated Carbon - Guru Balan, Lavanyha (Universiti Sains Malaysia, 2018)
Water pollution become an integral concern especially dye pollution which is waste generated by textile industry. In order to reduce the pollution caused by dyes, this study was conducted to determine the usage of chromium modified activated carbon (CMAC) for the adsorption of Acid Yellow 17 (AY 17) dye. Fixed bed adsorption study was conducted to investigate the optimum condition for adsorption of Acid Yellow 17 to occur. For the fixed bed adsorption study, the parameter that was studied was the effect of initial dye concentration (10-50 mg/L), inlet flow rate of AY 17 solution (10-30 mL/min) and bed height of adsorbent (2-4 cm). For the effect of initial dye concentration, the breakthrough time was the fastest for 50 mg/L and 40 mg/L. For the effect of inlet flow rate of AY17 solution, the breakthrough curve becomes steeper as the inlet flow rate of dye solution increases. For the effect of bed height of adsorbent, the breakthrough time increases as the bed height increases. Column dynamics was also studied and the model used was Thomas, Yoon-Nelson, Adams-Bohart, and BDST analysis model. Thomas, Yoon-Nelson and BDST analysis model fitted well the adsorption data as compared to Adams-Bohart model. For the in situ column regeneration study, the breakthrough time decreases and the slope of the curve becomes steeper as the CMAC undergoes series of regeneration. The adsorption capacity also decreases as the regeneration cycle is repeated a few times.